Case report: Subcutaneous Mycobacterium haemophilum infection in an immunocompetent patient after lipolysis injections - Ni, Linan; Zou, Danyang; Yang, Hong; Gao, Zhiqin; Yu, Qian; Yang, Lianjuan (Frontiers in Medicine, 2023)
Mycobacterium haemophilum is a slow-growing, aerobic mycobacterium that acts as a pathogen in immunocompromised adult patients and immunocompetent children. There are only a few rare cases in the literature describing this species as a cause of subcutaneous infections. Here, we describe a subcutaneous infection caused by M. haemophilum in an immunocompetent female after lipolysis injections at an unqualified beauty salon, suggesting that this bacteria can also be a potential causative agent of adverse events in medical aesthetics. In addition, M. haemophilum caused lesions not only at the injection sites and adjacent areas but also invaded distant sections through the subcutaneous sinus tracts. Thus, early diagnosis and appropriate treatment are vital to prevent further deterioration and improve prognosis.